ANALISIS PRODUKTIVITAS METODE PELAKSANAAN PENGECORAN BETON READY MIX PADA BALOK DAN PELAT LANTAI GEDUNG - Frederika, Ariany; Rai Widhiawati, Ida Ayu (JURNAL SPEKTRAN, 2017)
Abstract: Implementation method technology of multi-storey building concrete construction is experiencing significant growth, both in material processing and casting equipment.  Several casting equipment including concrete lift  and concrete pump have  different productivities  which contribute to time and cost.  This research aims to analyze the productivity of casting equipment, time and cost required, as well as the break-even point of casting method of ready mix concrete application on the beams and the floor slabs of buildings, particularly on the second- floor, third- floor and forth-floor using concrete lift and concrete pump. Data was obtained by conducting interviews and observations concerning casting implementation of building construction projects that use K-300 ready- mix concrete.  Regression and Correlation analysis are used to obtain time and cost comparison between both method of casting implementation, as well as Break Even Point analysis to obtain breakeven point of casting volume with regards to cost and time. The analysis showed that casting productivities  using lift on  first, second and third floor  are 7,166 m 3 /h, 5,945 m 3 /h, 5,125 m 3 /h, while the productivities using concrete pump on  first, second and third floor  are 36 m 3 /h, 30 m 3 /h , 24 m 3 /hour. Cost comparison of 1 m 3 increment of casting using concrete lift and concrete pump is  Rp. 99 330: Rp.19.000 (5.23: 1),  while time ratio is  8.272 minutes: 2,172 minutes (3.8: 1). Breakeven point analysis towards casting cost showed that the second floor which has volume greater than 95.89 m3,  using concrete pump method is more optimal than concrete-lift.
Keywords: casting method, productivity, concrete lift, concrete pump, regression analysis, breakeven point